Better webtypography for a better web - Latin, Matej, ....- (San Francisco : Blurb, 2023)
Better Web Typography for a Better Web is a book based on a top-rated online course explaining typography to people who build web sites-web designers and web developers. The author, Matej Latin, takes complex concepts such as vertical rhythm, modular scale and page composition, and explains them in an easy-to-understand way. The content of the book is accompanied by live code examples and the readers go through a process of designing and building an example website as they go through the book. This is a new typography book for a new medium, the rules haven't changed much, everything else has.
Keywords: Typography; Webdesign